Risk to rely on soil carbon sequestration to offset global ruminant emissions - Wang, Yue; de Boer, Imke J. M.; Persson, U. Martin; Ripoll-Bosch, Raimon; Cederberg, Christel; Gerber, Pierre J.; Smith, Pete; van Middelaar, Corina E. (Nature communications, 2023)
Carbon sequestration in grasslands has been proposed as an important means to offset greenhouse gas emissions from ruminant systems. To understand the potential and limitations of this strategy, we need to acknowledge that soil carbon sequestration is a time-limited benefit, and there are intrinsic differences between short- and long-lived greenhouse gases. Here, our analysis shows that one tonne of carbon sequestrated can offset radiative forcing of a continuous emission of 0.99 kg methane or 0.1 kg nitrous oxide per year over 100 years. About 135 gigatonnes of carbon is required to offset the continuous methane and nitrous oxide emissions from ruminant sector worldwide, nearly twice the current global carbon stock in managed grasslands. For various regions, grassland carbon stocks would need to increase by approximately 25% − 2,000%, indicating that solely relying on carbon sequestration in grasslands to offset warming effect of emissions from current ruminant systems is not feasible. While accounting for intrinsic differences between short- and long-lived greenhouse gases, solely relying on soil carbon sequestration in grasslands to offset warming effect of emissions from current ruminant systems is not feasible